The Effect of Cone Drill Variations on Agility in MBC (Malang Badminton Club) Badminton Athletes Aged 10-15 Years - Diana Puspita Sari; Mahmud Yunus (Indonesian Conditioning Coaches, 2025)
The purpose of this study was to examine the effect of variations in cone drill exercises on agility in MBC (Malang Badminton Club) badminton athletes aged 10-15 years, which was conducted by the researcher from September to November 2025. This study used an experimental design with a one-group pre-test and post-test. The sample involved in the study consisted of 10 male athletes aged 10-15 years who actively participated in training. Data were collected by measuring the subjects' agility levels before and after receiving the variation of cone drill exercises, and then the data were evaluated using the t-test method with the assistance of the SPSS software version 31. The analysis results indicated that the calculated t-value (13.648) was greater than the table t-value (1.729) with a significance level of less than 0.001. These findings indicate a significant difference in the agility of athletes before and after being given cone drill training variations. In conclusion, variations in cone drill training show an impact on improving agility in MBC (Malang Badminton Club) badminton athletes aged 10-15 years. This is proven effective with accurate and responsive footwork, allowing the shuttlecock from the opponent's direction to be returned spontaneously, strengthening the athlete's ability to maintain balance during movement or sudden stops. This study contributes to the development of physical training programs, particularly in badminton, and can serve as a reference for coaches in designing programs focused on enhancing agility.